Associations of children’s math and gender beliefs with their math outcomes - Foo, Xiao Hui (Nanyang Technological University, 2021)
Past research has attributed the female underrepresentation in the Science, Technology, Engineering and Mathematics (STEM) fields to the field-specific ability beliefs (FAB) prevalent in those fields. The FAB hypothesis states that the belief that raw brilliance is essential to succeed in STEM fields (i.e., math = brilliance), coupled with the stereotype that males possess more natural talent than females (i.e., brilliance = male), may lower girls’ involvement in STEM fields. To our knowledge, the FAB hypothesis has not been examined on children, an important age group where individuals’ aspirations begin to emerge. Hence, this study aimed to assess how the FAB hypothesis is related to children’s math-related outcomes (i.e., math self-efficacy, interest, achievement, and aspiration) in the Singaporean context. The present research recruited 458 participants aged 6 to 16 (222 boys). Findings revealed that boys and girls endorsed both implicit and explicit math-brilliance beliefs, and the gender-brilliance stereotype. Consistent with the FAB hypothesis, children’s math = brilliance belief interacted with their gender to predict their math self-efficacy and aspiration (i.e., positive for boys and negative for girls). Thus, with the early emergence of the math-brilliance beliefs, and the associations between these beliefs and children’s math outcomes, it is imperative to develop an early intervention to encourage girls’ involvement in STEM fields.